A novel insertional allele of the CG18135 gene is associated with severe mutant phenotypes in Drosophila melanogaster - Ratiu, Attila Cristian; Ionascu, Adrian; Ecovoiu, Alexandru Al. (Frontiers in Genetics, 2024)
Drosophila melanogaster has been at the forefront of genetic studies and biochemical modeling for over a century. Yet, the functions of many genes are still unknown, mainly because no phenotypic data are available. Herein, we present the first evidence data regarding the particular molecular and other quantifiable phenotypes, such as viability and anatomical anomalies, induced by a novel PlacW insertional mutant allele of the CG18135 gene. So far, the CG18135 functions have only been theorized based on electronic annotation and presumptive associations inferred upon high-throughput proteomics or RNA sequencing experiments. The descendants of individuals harboring the CG18135PlacWCG18135 allele were scored in order to assess mutant embryonic, larval, and pupal viability versus Canton Special (CantonS). Our results revealed that the homozygous CG18135PlacWCG18135/CG18135PlacWCG18135 genotype determines significant lethality both at the inception of the larval stage and during pupal development. The very few imago escapers that either breach or fully exit the puparium exhibit specific eye depigmentation, wing abnormal unfolding, strong locomotor impairment with apparent spasmodic leg movements, and their maximum lifespan is shorter than 2 days. Using the quantitative real-time PCR (qRT-PCR) method, we found that CG18135 is upregulated in male flies, but an unexpected gene upregulation was also detected in heterozygous mutants compared to wild-type flies, probably because of regulatory perturbations induced by the PlacW transposon. Our work provides the first phenotypic evidence for the essential role of CG18135, a scenario in accordance with the putative role of this gene in carbohydrate-binding processes.